2018
DOI: 10.3389/fpsyg.2018.01180
|View full text |Cite
|
Sign up to set email alerts
|

Reading Self-Concept and Reading Anxiety in Second Grade Children: The Roles of Word Reading, Emergent Literacy Skills, Working Memory and Gender

Abstract: Background: Most studies in the field of reading have focused on the linguistic and cognitive factors. Less is known about the affective aspects of reading in young readers, such as self-perceptions of reading, and reading anxiety.Aims: This study aimed to shed light on the direct and indirect relations between reading and related skills (working memory, emergent literacy skills, word reading accuracy and rate, and gender) as sources of reading affect (reading self-concept and anxiety).Sample: A total of 115 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 106 publications
8
46
3
1
Order By: Relevance
“…This finding corroborates results from the Zbornik (1988) study using the original 45-item scale and contemporary research on reading anxiety (Katzir, Kim, & Dotan, 2018;Ramirez et al, 2019). The association between reading anxiety and reading performance reinforces the concept that the reading anxiety scale is measuring a concept associated with reading skills and highlights the importance of emotional aspects evaluation for a better understanding of school performance (Davis, Margolis, Thomas, Huo, & Marsh, 2018;Hendren, Haft, Black, White, & Hoeft, 2018;Jarrett, Black, Grills-Taquechel, & Ollendick, 2015;Katzir et al, 2018;Ramirez et al, 2019;Steinmayr et al, 2016). This study has limitations which we plan to overcome with future studies.…”
Section: Discussionsupporting
confidence: 87%
“…This finding corroborates results from the Zbornik (1988) study using the original 45-item scale and contemporary research on reading anxiety (Katzir, Kim, & Dotan, 2018;Ramirez et al, 2019). The association between reading anxiety and reading performance reinforces the concept that the reading anxiety scale is measuring a concept associated with reading skills and highlights the importance of emotional aspects evaluation for a better understanding of school performance (Davis, Margolis, Thomas, Huo, & Marsh, 2018;Hendren, Haft, Black, White, & Hoeft, 2018;Jarrett, Black, Grills-Taquechel, & Ollendick, 2015;Katzir et al, 2018;Ramirez et al, 2019;Steinmayr et al, 2016). This study has limitations which we plan to overcome with future studies.…”
Section: Discussionsupporting
confidence: 87%
“…The third hypothesis of DIER is interactive relationscomponent skills are expected to develop interacting with each other and environments (e.g., Ford & Lerner, 1992). Studies have shown that motivation and affect (e.g., reading motivation, attitudes, self-concept, efficacy, anxiety) predict reading achievement (e.g., L. Baker & Wigfield, 1999;Katzir et al, 2009;Wigfield & Guthrie, 1997) and that reading skills predict motivation and affect (Chapman & Tunmer, 2003;Katzir et al, 2018). Indeed, longitudinal studies have shown bidirectional relations of motivation and affect with reading development (Lepola et al, 2000).…”
Section: Interactive Relations Hypothesis Of Diermentioning
confidence: 99%
“…It consists of the ability to recover and name familiar items fluently, evaluating the speed and accuracy in the process of accessing the lexicon (Heikkilä, 2015). Slow performance on RAN tasks is associated with poor reading performance (Denkla and Rudel, 1976;Lúcio et al, 2017;Katzir et al, 2018;Landerl et al, 2019). Several studies confirm that RAN has a strong correlation with reading competence, with a progressively more relevant role throughout the school path (Cohen et al, 2018).…”
Section: Introductionmentioning
confidence: 98%